The Effectiveness of Using AI Gemini in Learning Chronological Essay Writing Among Second-Semester Students at Universitas Bhinneka PGRI - Adinda Muslimah Wahyuning Triasmoro; Ika Rakhmawati (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study aimed to measure the effectiveness of using AI Gemini in improving the writing ability of chronological essays among second-semester students of the English Education Department at Universitas Bhinneka PGRI. A quantitative approach with a pre-experimental one-group pretest-posttest design was applied. The instruments used were writing tests administered before and after the treatment. Data were analyzed using SPSS version 26 through descriptive statistics, normality testing, and hypothesis testing. The results indicated a significant improvement in the post-test scores, with a significance value (2-tailed) of 0.000 (<0.05). The mean pre-test score of 66.50 increased to 85.00 in the post-test. These findings demonstrate that the use of AI Gemini is effective in supporting students to improve their writing skills, particularly in grammar accuracy, sentence structure, vocabulary, and text coherence. This study also emphasizes the importance of applying AI tools in a balanced way to foster critical thinking and independent writing skills.